Longitudinal diffusion weighted imaging of limbic regions in patients with major depressive disorder after 6 years and partial to full remission. (30th May 2019) - Doolin, Kelly; Andrews, Sinaoife; Carballedo, Angela; McCarthy, Hazel; O'Hanlon, Erik; Tozzi, Leonardo; Frodl, Thomas
Highlights: Both MDD patients and HCs showed reduced FA in the regions of interest, indicative of tract integrity reduction, at the 6-year follow-up scan. There was a significant effect of MDD diagnosis on longitudinal FA of the left dorsal cingulum and left parahippocampal cingulum. The reduction of left rostral cingulum and right uncinate fasciculus FA were inversely related to HAM-D improvement within the MDD group. Abstract: The objective of this study was to determine the effect of major depressive disorder (MDD) on white matter microstructures after a 6-year period compared to healthy controls (HC). This study included a small sample size of 26 participants, including 14 patients with MDD clinically diagnosed at baseline, and 12 HCs. MRI brain scans were conducted at baseline and follow-up, 75.32 (±2.25) months after the initial scan. Tractography of 7 regions including the fornix, cingulum, superior longitudinal fasciculus, inferior fronto-occipital fasciculus and uncinate fasciculus were conducted using ExploreDTI software. Both groups showed significant reduction in tract integrity between time points. MDD diagnosis was shown to have an effect on longitudinal FA of the left dorsal cingulum and the left parahippocampal cingulum. A significant inverse relationship was found between ΔFA [baseline FA – follow-up FA] of the right uncinate fasciculus and the left rostral cingulum with ΔHAM-D [baseline HAM-D – follow-up HAM-D] within the MDD group. These preliminary findings support the hypothesis that limbic structures including the cingulum are involved in MDD pathophysiology and may be affected even after remission. Moreover, they indicate that recovery from depression symptoms may slow the rate of WM degradation associated with aging in these regions of interest.